2016
DOI: 10.3892/ol.2016.5208
|View full text |Cite
|
Sign up to set email alerts
|

Expression of semaphorin 6D and its receptor plexin-A1 in gastric cancer and their association with tumor angiogenesis

Abstract: Abstract. The semaphorin and plexin family of ligands and receptor proteins provides important axon growth and guidance cues required for development. In recent years, studies have expanded their role in the regulation of cardiac morphogenesis and tumorigenesis. However, the mechanism responsible for their role in regulating cancer development and progression has not been clarified. In the present study, semaphorin 6D (Sema6D) and its receptor plexin-A1 were identified to be expressed at high levels in vascula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…SEMA6D has been reported to be highly expressed in vascular epithelial cells in gastric cancer; it was also positively correlated with the expression of vascular endothelial growth factor receptor 2 (VEGFR2). Therefore, SEMA6D may be associated with tumor angiogenesis [ 49 , 50 ]. The HADHB gene encodes the beta subunit of a mitochondrial trifunctional protein that catalyzes the last three steps of mitochondrial beta-oxidation of long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…SEMA6D has been reported to be highly expressed in vascular epithelial cells in gastric cancer; it was also positively correlated with the expression of vascular endothelial growth factor receptor 2 (VEGFR2). Therefore, SEMA6D may be associated with tumor angiogenesis [ 49 , 50 ]. The HADHB gene encodes the beta subunit of a mitochondrial trifunctional protein that catalyzes the last three steps of mitochondrial beta-oxidation of long-chain fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, bio‐signal analysis has revealed that the SEMA6D gene may play an important role in promoting the OS of patients with breast cancer 28 . Studies have shown that the SEMA6D gene is directly related to the presence of VEGFR2 in the angiogenesis of gastric cancer, which plays an important pathogenic role 29 . Studies on esophageal cancer have identified that SEMA6D is a target gene that is upregulated by hsa‐miR‐1 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In models of gastric cancer, signaling due to Sema6D and Plexin-A1/VEGFR2 interaction results in effects similar to VEGF binding alone. In addition, Sema6D/Plexin-A1 expression is positively correlated with the expression of VEGFR2, therefore contributing to its angiogenic and tumorigenic properties (59). Poor prognosis of gastric cancer has been correlated with Sema6D expression and increased angiogenesis (59) ( Table 1).…”
Section: Role Of Semaphorins In Angiogenesismentioning
confidence: 99%